Density Functional Theory calculations and Vibrational assignment of Trimethylhydroquinone (TMHQ) - P.S. Joseph, N. Raghothaman* and (Recent Research in Science and Technology, 2010)
The spectroscopic techniques are very effective and sensitive tool for study of atomic and molecular structure and also used for qualitative and quantitative analysis of compounds. The Fourier transform infrared and Fourier transform Raman spectra of Trimethyl hydroquinone have been recorded in the region 4000-400 cm-1 and 3500-50 cm-1 respectively. The equilibrium geometry harmonic vibrational frequencies, infrared intensities and Raman scattering activities were calculated with Density Functional B3LYP method with 6-31+G(d,p) and 6-311++G(d,p) basis set combination. A detailed interpretation of the infrared and Raman spectra of Trimethylhydroquinone is reported. Our calculated vibrational frequencies are in good agreement with experimental wavenumbers.